Agroforestry Models: Social, Agronomic, and Environmental Validation in Arboledas, Norte de Santander - Flórez Delgado, Dixon Fabián; Castellanos González, Leónides; Capacho Mogollón, Alfonso Eugenio (2025)
The project “Strategic agroecological development with the use of ICT to strengthen promising crops in the department of Norte de Santander” aimed to validate three agroforestry models in the municipality of Arboledas for 18 months, with the participation of 15 producers, benefiting 90 families. Three models were established: Model 1 (Cedar–lemon–corn), Model 2 (Cedar–avocado–corn) and Model 3 (Cedar avocado–bean). Regarding water quality, the models reduced heavy metals such as zinc and copper, although ammonia and manganese were increased. Soil analyzes revealed high agrochemical variability in Model 3, with more than 60% variation in 15 of 22 parameters. For soil biology, 3,249 individuals of macrofauna, 3,981 of mesofauna and 1,555 of microfauna were identified, with improvements in biodiversity observed after its implementation. In plant growth, there were no differences between control and agroecological plots for lemon and avocado. The pests had a low incidence, except for the armyworm in Model 2. Model 3 did not present phytosanitary effects. Finally, the social impact was positive thanks to the transfer of knowledge through ICT, improving the profitability, sustainability and quality of life of the benefited communities.
Keywords: Soil biology; Water quality; Agricultural production; Sustainability; Knowledge transfer